Brand Positioning and Psychological Ownership: A Study on Yamaha, Honda and Suzuki Motorcycles in Indonesia - Sutisna, Sutisna; Rustandi, Tata (International Journal of Multidisciplinary Research and Literature, 2024)
Brand positioning is crucial for marketers because strong brand positioning will make the brand easy to remember by consumers. This study aims to find out how strong the brand positioning of Yamaha, Honda and Suzuki motorcycles is in Indonesia. In addition, they also want to know the brand positioning of certain brands related to ownership, especially psychological ownership. The number of respondents in this study was 398, and the analysis method used was a paired average difference test and one-way ANOVA. The study results show that Honda's brand positioning is stronger than Yamaha and Suzuki. Only Honda owners consider Honda to have a stronger brand positioning than Yamaha and Honda. Yamaha and Suzuki owners consider that the brand positioning of Yamaha and Suzuki is not different between the two and with Honda